Beispiel Nr: 04
$ D_h=\begin{array}{|cc|}a1\ & b1 \\ a2&b2 \\ \end{array}= a1 \cdot b2 -b1 \cdot a2 \\ D_x=\begin{array}{|cc|}c1\ & b1 \\ c2&b2 \\ \end{array}= c1 \cdot b2 -b1 \cdot c2 \\ D_y=\begin{array}{|cc|}a1\ & c1 \\ a2&c2 \\ \end{array}= a1 \cdot c2 -c1 \cdot a2\\ x=\frac{D_x}{D_h} \\ y=\frac{D_y}{D_h} \\ \\ \textbf{Gegeben:} \\ \\ 9 x -2 y =1\\ -3 x -3 y = -7 \\ \\ \\ \\ \textbf{Rechnung:} \\ D_h=\begin{array}{|cc|}9\ & -2 \\ -3&-3 \\ \end{array}= 9 \cdot \left(-3\right) -\left(-2\right) \cdot \left(-3\right)=-33 \\ D_x=\begin{array}{|cc|}1\ & -2 \\ -7&-3 \\ \end{array}= 1 \cdot \left(-3\right) -\left(-2\right) \cdot \left(-7\right)=-17 \\ D_y=\begin{array}{|cc|}9\ & 1 \\ -3&-7 \\ \end{array}= 9 \cdot \left(-7\right) -1 \cdot \left(-3\right)=-60 \\ \ x=\frac{-17}{-33} \\ x=\frac{17}{33} \\ y=\frac{-60}{-33} \\ y=1\frac{9}{11} \\ L=\{\frac{17}{33}/1\frac{9}{11}\}\\ \, $